2002
DOI: 10.1161/01.res.0000024389.03152.22
|View full text |Cite
|
Sign up to set email alerts
|

Actin Capping Protein

Abstract: Abstract-Actin capping protein (CapZ) binds the barbed ends of actin at sarcomeric Z-lines. In addition to anchoring actin, Z-discs bind protein kinase C (PKC). Although CapZ is crucial for myofibrillogenesis, its role in muscle function and intracellular signaling is unknown. We hypothesized that CapZ downregulation would impair myocardial function and disrupt PKC-myofilament signaling by impairing PKC-Z-disc interaction. To test these hypotheses, we examined transgenic (TG) mice in which cardiac CapZ protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 43 publications
2
35
0
Order By: Relevance
“…In the current study, capping protein ␣1 was highly correlated with HW/BW (Table IV). Capping protein ␤1 was reported to be a critical element in protein kinase C signaling to cardiac myofilaments (74). The current study suggests that capping protein ␣ 1 may play an important role in IGF1R-PI3K(p110␣) signaling to cardiac myocytes.…”
Section: Igf1r Induces Physiological Cardiac Growth Via Pi3k(p110␣)mentioning
confidence: 58%
“…In the current study, capping protein ␣1 was highly correlated with HW/BW (Table IV). Capping protein ␤1 was reported to be a critical element in protein kinase C signaling to cardiac myofilaments (74). The current study suggests that capping protein ␣ 1 may play an important role in IGF1R-PI3K(p110␣) signaling to cardiac myocytes.…”
Section: Igf1r Induces Physiological Cardiac Growth Via Pi3k(p110␣)mentioning
confidence: 58%
“…Desmin phosphorylation by PKC has been linked to myofibril disarray and cardiomyopathy in hamsters, but the isoform(s) of PKC involved and the role of anchoring proteins remain unknown. Very recently, Pyle et al reported that phenylephrine-mediated myofilament/ε-PKC association was decreased in transgenic mice with reduced actin capping protein (CapZ), suggesting that the Z-line-associated CapZ might serve as a useful target in the management of myofilament function by PKC (Pyle et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…They are central to maintaining sarcomere geometry, integrating force, and transmitting tension, so it is reasonable that they could also modulate Ca 2+ -dependent contraction. For example, modifying the Z-disk proteins Cap-Z (reducing expression) or muscle LIM protein (MLP) (acetylation) increases calcium sensitivity (49,50). In skeletal muscle, reducing Z-disk or M-band stiffness reduces calcium sensitivity (51), while genetic mutations in Z-disk proteins result in cardiomyopathy associated with Z-disk destabilization (52) and/or changes in myofilament stiffness and Ca 2+ response (53).…”
Section: Figurementioning
confidence: 99%